Protein targeting via the "constitutive-like" secretory pathway in isolated pancreatic islets: passive sorting in the immature granule compartment (The Rockefeller University Press, 1992)
We have suggested the existence of a novel "constitutive-like" secretory pathway in pancreatic islets, which preferentially conveys a fraction of newly synthesized C-peptide, insulin, and proinsulin, and is related to the presence of immature secretory granules (IGs). Regulated exocytosis of IGs results in an equimolar secretion of C- peptide and insulin; however an assay of the constitutive-like secretory pathway recently demonstrated that this route conveys newly synthesized C-peptide in molar excess of insulin (Arvan, P., R. Kuliawat, D. Prabakaran, A.-M. Zavacki, D. Elahi, S. Wang, and D. Pilkey. J. Biol. Chem. 266:14171-14174). We now use this assay to examine the kinetics of constitutive-like secretion. Though its duration is much shorter than the life of mature granules under physiologic conditions, constitutive-like secretion appears comparatively slow (t1/2 approximately equal to 1.5 h) compared with the rate of proinsulin traffic through the ER and Golgi stacks. We have examined whether this slow rate is coupled to the rate of IG exit from the trans-Golgi network (TGN). Escape from the 20 degrees C temperature block reveals a t1/2 less than or equal to 12 min from TGN exit to stimulated release of IGs; the time required for IG formation is too rapid to be rate limiting for constitutive-like secretion. Further, conditions are described in which constitutive-like secretion is blocked yet regulated discharge of IGs remains completely intact. Thus, constitutive-like secretion appears to represent an independent secretory pathway that is kinetically restricted to a specific granule maturation period. The data support a model in which passive sorting due to insulin crystallization results in enrichment of C-peptide in membrane vesicles that bud from IGs to initiate the constitutive-like secretory pathway.